COASTAL VULNERABILITY ANALYSIS IN DUMAI BARAT DISTRICT - Butarbutar, Yesenia Nancy Olivia; Mubarak, Mubarak; Wibowo, Muhammad Arief (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The Coastal area is an area that is very vulnerable to the phenomenon of natural change. The coastal area's vulnerability level is influenced by geological variables, namely coastal geomorphology, sea level rise, shoreline changes, tides, and coastal elevations. This research was conducted in October 2021. This study aims to determine the level of coastal vulnerability in the Dumai Barat Sub-District, Riau Province with a quantitative descriptive method. Based on the result of the study, the coastal vulnerability index can be classified into five categories: very not vulnerable, not vulnerable, medium, high, and very high. The coastal area of Dumai Barat District is categorized as low vulnerability.